Development of Vibrio harveyi protease deletion mutant as live attenuated vaccine against vibriosis in Epinephelus fuscoguttatus (Forsskal, 1775) - Mohd Aris, Aslizah (2018)
Groupers aquaculture industries have faced a high risk of bacterial diseases such as Vibriosis. Various types of vaccine have been studied including attenuated vaccine. However, the potential of live attenuated vaccine is still understudied. This study was conducted to develop a live attenuated protease derivative from pathogenic Vibrio harveyi strain Vh1 as a live vaccine candidate using site-directed mutagenesis (SDM) and allelic exchange replacement techniques. In SDM, an overlapping PCR was performed to generate a deletion in a specific amino acid residue that represents a catalytic site of the protease gene. Seven mutant variants consisted of single deletion catalytic sites (DelD, DelH, and DelS), double deletion catalytic sites (DelDDelH, DelDDelS and DelHDelS) and triple mutation catalytic sites (DelDDelHDelS) were successfully developed. Evaluation of protease activity showed DelDDelHDelS recombinant recorded highest relative protease activity. A mutagenesis plasmid was further constructed using pRE112 as suicide plasmid, prior to the transformation into E. coli SM10pir. The resulting mutagenesis plasmid (pRE112-DelDDelHDelS) was integrated into the chromosome of V. harveyi strain Vh1 by employing a combined mixed broth-membrane filter technique for conjugation and the allelic replacement technique. Subsequently, the attenuated strain was designated as V. harveyi attenuated strain MVh-vhs and was further used as live vaccine candidate throughout this study. In vivo study was performed in Epinephelus fuscoguttatus to evaluate the safety and pathogenicity level of the attenuated strain. Fish challenged with the parental strain showed obvious clinical signs of Vibriosis such as hemorrhages on the ventral abdominal pelvic area, external lesion and white depigmentation in skin. The median lethal dosage (LD50) in fish challenged with the parental strain was found at 106 CFU/fish. Histopathological analysis showed the presence of immunological response activity in both fish treatment. In contrast, 100% survival with no indication of vibriosis was detected in fish challenged with the attenuated strain. Vaccination with the attenuated strain in juvenile E. fuscoguttatus was performed using a single dose IP administration at 105 CFU/fish. The bacterial challenge was done after four weeks post vaccination with the pathogenic V. harveyi strain Vh1 at dosage concentration of 108 CFU/fish following IP administration. Fish vaccinated with the attenuated strain showed 52% relative percentage survival (RPS). De novo transcriptomic analysis revealed that the vaccinated E. fuscoguttatus with the attenuated strain conferred both innate and adaptive immunity. The innate adaptive involved in regulation of the autophagosome pathway and coagulation and complement cascade pathway. Adaptive immunity relies on the regulation of antigen processing and presentation pathway. In addition, V. harveyi attenuated strain MVh-vhs possessed an unmarked gene deletion and the attenuation properties were found stable after 15 in vitro passages. As a conclusion, the V. harveyi attenuated strain MVh-vhs has significant potential to be applied as a live vaccine candidate against vibriosis in E. fuscogutattus.